Primary vulval melanoma and genital lichen sclerosus - Evanthia Mastoraki; Georgios Kravvas; Kate Dear; Sharmaine Sim; Mariel James; Richard Watchorn; Aiman Haider; Peter Ellery; Alex Freeman; Mahfooz Basha; Emma Edmonds; Christopher B. Bunker (Wiley, 2024)
Abstract Background Lichen sclerosus (LS) is a chronic, inflammatory skin disease with a predilection for the genitalia. Although, the association between squamous cell cancer and genital LS is well established, a link with genital melanoma has not been thoroughly explored. However, we have recently published a case series of penile melanoma where 9/11 (82%) of patients seen over a 10 year period with penile melanoma were retrospectively found to have histological and/or clinical evidence of genital LS on review. Objectives The aim of this study was to illuminate further the relationship between vulval melanoma and genital LS by reviewing all the cases managed by our hospital and undertaking a literature review. Methods We identified all the cases with a diagnosis of vulval melanoma over a 16‐year period (2006-2022) where histology was available. The clinical notes were retrospectively reviewed, and the histological features of all cases were reassessed by two independent mutually 'blinded' histopathologists. We also performed a literature review of genital LS in patients with vulval melanoma. Results A total of 11 patients with vulval melanoma were identified for the review. Histopathological review found evidence of genital LS in seven of them (64%). Genital LS was not documented in any of the original histology reports. Clinical notes and letters were available in nine cases. The literature review identified 12 relevant studies with a total of 18 patients. Twelve cases concerned adult women, and six concerned female children. Conclusion The presence of genital LS in as high as 64% of our vulval melanoma cases might indicate a causative relationship between genital LS and vulval melanoma. The pathogenesis of vulval melanoma remains largely unknown. Although ultraviolet radiation is an important pathogenic factor for cutaneous melanoma, it cannot be a factor in vulval melanoma. While possible mechanisms behind this association remain unclear, it is possible that chronic inflammation from genital LS leads to melanocytic distress and increased mutagenesis.